Faktor-Faktor yang Mempengaruhi Efektivitas Non Aktifnya Trayek Bus Trans Kota di Bandar Lampung - Setiadi, Hafidh Danang; Pramita, Galuh; Ariyanto, Lilik (Universitas Batanghari Jambi, 2025)
Bandar Lampung City is one of the developing cities that has transportation problems, especially mass transportation or public transportation. Existing public transportation, such as city buses and city transportation, is not very efficient for its users. This is because the safety and comfort factors are so lacking that people prefer to use private vehicles compared to public transportation. The purpose of this study was to determine the main factors that influence the inactivity of the Trans City Bus route in Bandar Lampung City and to determine the level of user satisfaction with the Bandar Lampung Trans City Bus service using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA) data analysis methods. The results of this study explain that the main factor causing the inactivity of the Trans City Bus route in Bandar Lampung City is competition with online transportation. Results using the IPA method In quadrant 1, there are 11.11% of respondents who feel that the performance level of these facilities and services is high, In quadrant 2, there are 55.56% Respondents who feel that these facilities and services are very important with a high level of performance. In quadrant 3, there are 22.22% of respondents who feel that these facilities and services are relatively low with a low level of performance.In quadrant 4, there are 11.11% of respondents who feel that these facilities and services are very important, with CSI showing the results of users being satisfied with the satisfaction index value reaching 0.734%.